Pengaruh Hubungan Komunikasi antara Atasan dan Bawahan serta Motivasi terhadap Kinerja Pegawai di Kantor Dinas Pertanian Kabupaten Pidie Jaya - Izazaya, M.; Ikhbar, Samsul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Employee performance can be influenced by the smooth communication within an organization, particularly the relationship between superiors and subordinates. Additionally, work motivation plays a crucial role in driving employees to perform better, ultimately impacting their performance. This study aims to examine the effect of superior-subordinate communication and motivation on employee performance at the Agriculture Office of Pidie Jaya Regency. The respondents consisted of 54 employees who provided data through questionnaires, which were then analyzed using multiple linear regression. The results indicate that both superior-subordinate communication and work motivation positively affect employee performance. Among these factors, work motivation has a stronger influence. 66.7% of employee performance is influenced by superior-subordinate communication and motivation, while the remaining percentage is affected by other factors. Statistical testing shows that the F value is greater than the F table, and the t value is greater than the t table, indicating that both variables significantly influence employee performance, both simultaneously and partially. Based on these findings, the alternative hypothesis (Ha) is accepted, while the null hypothesis (Ho) is rejected. Employee performance at the Agriculture Office of Pidie Jaya Regency is influenced by communication and work motivation.